Implementation of the diversification strategy for the formation of the adaptability of the enterprise - Курбацька, Лариса Миколаївна; Kurbatska, Larysa; Квасова, Людмила Сергіївна; Kvasova, Luidmyla; Лозовий, Денис Володимирович; Lozovyi, Denys (My University, 2024)
The purpose of this paper is to explore the significance of production diversification as a strategic approach for enhancing the adaptability and resilience of enterprises in a volatile economic environment. It aims to analyze the various diversification strategies available to businesses, assess the associated risks and opportunities, and identify the key factors that influence the selection of an optimal diversification strategy. Through this exploration, the paper underscores the importance of diversification in securing the long-term viability and success of enterprises in today's dynamic marketplace. Metodology of the paper. The methodology of this paper involves a comprehensive approach to exploring production diversification as a strategic tool for enhancing enterprise adaptability and resilience. A thorough review of existing literature on production diversification, adaptability, and resilience in enterprises will be conducted. This will include academic articles, industry reports, and case studies to establish a theoretical framework and identify best practices. In-depth interviews and surveys will be conducted with business leaders and industry experts to gather insights on their experiences with diversification strategies. This qualitative data will help to understand the practical challenges and successes associated with implementing diversification. Recommendations. Based on the findings, practical recommendations will be formulated for business leaders on how to select and implement optimal diversification strategies to enhance adaptability and resilience. Limitations and Future Research: The paper will also discuss the limitations of the study and suggest areas for future research to further explore the topic of production diversification. This methodology aims to provide a holistic understanding of production diversification and its significance in navigating the complexities of the modern economic landscape. Results. The results of the study indicate that companies that actively engage in production diversification tend to exhibit greater adaptability and resilience in volatile markets. Analysis of case studies revealed that successful diversification strategies often involve a combination of product innovation and market expansion. Qualitative insights from industry leaders highlighted the importance of aligning diversification efforts with core competencies to mitigate risks. Practical implicatrions. The practical implications of this study suggest that businesses should prioritize production diversification as a key strategy for enhancing adaptability and resilience in changing market conditions. Value / originality. The originality of this study lies in its comprehensive approach to understanding production diversification, integrating both qualitative and quantitative analyses to provide a well-rounded perspective. By synthesizing insights from industry leaders, case studies, and statistical data, the research offers actionable recommendations that are grounded in real-world experiences. Метою цієї статті є дослідження значення диверсифікації виробництва як стратегічного підходу для підвищення адаптивності та стійкості підприємств у нестабільному економічному середовищі. Його метою є аналіз різноманітних стратегій диверсифікації, доступних для бізнесу, оцінка пов’язаних ризиків і можливостей, а також визначення ключових факторів, які впливають на вибір оптимальної стратегії диверсифікації. Завдяки цьому дослідженню документ підкреслює важливість диверсифікації для забезпечення довгострокової життєздатності та успіху підприємств на сучасному динамічному ринку. Методика роботи. Методологія цієї статті передбачає комплексний підхід до вивчення диверсифікації виробництва як стратегічного інструменту підвищення адаптивності та стійкості підприємства. Буде проведено ретельний огляд існуючої літератури щодо диверсифікації виробництва, адаптивності та стійкості підприємств. Це включатиме академічні статті, галузеві звіти та тематичні дослідження для встановлення теоретичної основи та визначення передового досвіду. Будуть проведені детальні інтерв’ю та опитування з лідерами бізнесу та експертами галузі, щоб отримати інформацію про їхній досвід застосування стратегій диверсифікації. Ці якісні дані допоможуть зрозуміти практичні проблеми та успіхи, пов’язані з впровадженням диверсифікації. Рекомендації. На основі отриманих результатів будуть сформульовані практичні рекомендації для бізнес-лідерів щодо вибору та впровадження оптимальних стратегій диверсифікації для підвищення адаптивності та стійкості. Обмеження та майбутні дослідження: у документі також обговорюватимуться обмеження дослідження та запропоновані напрямки майбутніх досліджень для подальшого вивчення теми диверсифікації виробництва. Ця методологія має на меті забезпечити цілісне розуміння диверсифікації виробництва та її значення для подолання складних умов сучасного економічного ландшафту. Результати. Результати дослідження показують, що компанії, які активно займаються диверсифікацією виробництва, як правило, демонструють більшу адаптивність і стійкість на нестабільних ринках. Аналіз тематичних досліджень показав, що успішні стратегії диверсифікації часто передбачають поєднання інноваційної продукції та розширення ринку. Якісні висновки лідерів галузі підкреслили важливість узгодження зусиль з диверсифікації з основними компетенціями для зменшення ризиків. Практичні наслідки. Практичні наслідки цього дослідження свідчать про те, що підприємства повинні віддавати пріоритет диверсифікації виробництва як ключовій стратегії для підвищення адаптивності та стійкості до мінливих ринкових умов. Цінність / оригінальність. Оригінальність цього дослідження полягає в його комплексному підході до розуміння диверсифікації виробництва, який поєднує як якісний, так і кількісний аналіз, щоб забезпечити всебічну перспективу. Завдяки синтезу думок лідерів галузі, тематичних досліджень і статистичних даних дослідження пропонує дієві рекомендації, які ґрунтуються на реальному досвіді.
Реалізація стратегії диверсифікації для формування адаптаційності підприємства
Keywords: iversification; диверсифікація; enterprise; підприємство; risk mitigation; зниження ризиків; strategic planning; стратегічне планування; resource allocation; розподіл ресурсів; market dynamics; динаміка ринку